OP0002 INCIDENCE OF FIRST CARDIOVASCULAR EVENT IN SPANISH PATIENTS WITH CHRONIC INFLAMMATORY RHEUMATIC DISEASES: PROSPECTIVE DATA FROM THE CARMA PROJECT AFTER 5 YEARS OF FOLLOW-UP. (2nd June 2020) - Martin-Martinez, M. A.; Castañeda, S.; Sánchez-Alonso, F.; García Gomez, C.; Gonzalez Juanatey, C.; Belmonte, M. A.; Tornero, J.; Santos Rey, J.; Sanchez Gonzalez, C. O.; Quesada-Masachs, E.; Moreno Gil, M. D.; Cobo-Ibáñez, T.; et al.
Abstract : Objectives: To determine the incidence and risk factors implicated in the development of first cardiovascular (CV) event (CVE) in patients with chronic inflammatory rheumatic diseases (CIRD) attending Spanish rheumatology clinics after 5 years of follow-up Methods: Analysis of data of patients included in an observational prospective study [CARdiovascular in rheuMAtology (CARMA) project] after 5 years of follow-up. The study includes a cohort of 2234 patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA), and another cohort of matched individuals (n=677) without CIRD from 67 hospitals in Spain. Cumulative incidence per 1000 patients of CVE was estimated in both cohorts at 5 years from the start. Weibull proportional hazard model was used to calculate the Hazard Ratio (HR) and 95% confidence intervals (CI) of the risk factors involved in the development of CV events. Losses to follow-up and their causes were also analyzed. Results: The total number patient who completed the follow-up visit at 5 years was 2.382 (81.9%). Fifteen patients died due to CVE and sixty due to non-CVE. The patients with CIRD showed higher cardiovascular cumulative incidence (40.5; 95% CI: 36.2-44.8) than controls (28.3; 95% CI: 21.8-34.8). The higher risk of developing a first CVE during the 5 years of follow-up was seen in patients with AS (HR: 4.60; 95% CI: 1.32-15.99; p=0.02), those with older age (HR:1.09; 95% CI: 1.05-1.13; p<0.001), higher systolic blood pressure (HR: 2.64; 95% CI: 1.32-5.25; p=0.006), and those with longer duration of the rheumatic disease (HR: 1.07; 95% CI: 1.03-1.12; p=0.002). In contrast, woman gender was a protective factor (HR: 0.45; 95% CI: 0.21-0.99; p=0.047). Conclusion: Patients with AS prospectively followed-up at rheumatology outpatient clinics showed higher risk of developing a first CVE than those without CIRD. Besides traditional CV disease risk factors, a longer time course of the disease is a risk factor for the development of CV disease in patients with CIRD. Acknowledgments: This project has been supported by an unrestricted grant from Abbvie, Spain. The design, analysis, interpretation of results and preparation of the manuscript has been done independently of Abbvie. Disclosure of Interests: Maria Auxiliadora Martin-Martinez: None declared, Santos Castañeda: None declared, Fernando Sánchez-Alonso: None declared, Carmen García Gomez: None declared, Carlos Gonzalez Juanatey: None declared, Maria Angeles Belmonte: None declared, Jesús Tornero: None declared, José Santos Rey: None declared, CARMEN OLGA SANCHEZ GONZALEZ: None declared, Estefanía Quesada-Masachs: None declared, MARIA DELPUERTO MORENO GIL: None declared, Tatiana Cobo-Ibáñez: None declared, Jose Antonio Pinto Tasende: None declared, Jesús Babío: None declared, Gemma Bonilla: None declared, Antonio Juan Mas: None declared, Javier Manero: None declared, Montserrat Romera: None declared, Javier Bachiller-Corral: None declared, Eugenio Chamizo Carmona: None declared, Javier Calvo: None declared, Raimon Sanmarti: None declared, Maria Celia Erausquin: None declared, Rosario Garcia de Vicuna Grant/research support from: BMS, Lilly, MSD, Novartis, Roche, Consultant of: Abbvie, Biogen, BMS, Celltrion, Gebro, Lilly, Mylan, Pfizer, Sandoz, Sanofi, Paid instructor for: Lilly, Speakers bureau: BMS, Lilly, Pfizer, Sandoz, Sanofi, Carmen Barbadillo: None declared, Sergio Ros Exposito: None declared, Javier del Pino Grant/research support from: Roche, Bristol, Consultant of: Gedeon, MARIA JOSE GONZALEZ: None declared, José Manuel Pina Salvador: None declared, Javier Llorca: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD